Answer ক. দেওয়া আছে,
`x^2 - 2sqrt(2) x + 1 = 0`
বা, `x^2 + 1 = 2sqrt(2) x`
বা, `x^2/x + 1/x = 2sqrt(2)` [x]
বা, `x + 1/x = 2sqrt(2)`
বা, `(x + 1/x)^2 = (2sqrt(2))^2`
বা, `(x - 1/x)^2 + 4.x.1/x = 8`
বা, `(x - 1/x)^2 + 4 = 8`
`:. (x - 1/x)^2 = 4` (Ans)
খ. প্রদত্ত রাশি` = (x^8 + 1)/x^4`
` = x^8/x^4 + 1/x^4 `
`= x^4 + 1/x^4 `
`= (x^2)^2 + (1/x^2)^2`
`= (x^2 + 1/x^2)^2 - 2x^2. 1/x^2`
`= {(x - 1/x)^2 + 2.x.1/x}^2 - 2`
`= (4 + 2)^2 - 2` [:. `(x - 1/x)^2 = 4`]
`= (6)^2 - 2 `
`= 36 - 2`
= 34 (Ans)
গ. ‘ক’ হতে পাই,
`(x - 1/x)^2 = 4`
`:. x - 1/x = 2 [:. x > 0]`
এখন, `(x^3 - 1/x^3) (x^2 + 1/x^2)`
`= x^5 + x - 1/x - 1/x^5`
বা,`x^5 - 1/x^5 = (x^3 - 1/x^3) (x^2 + 1/x^2) - (x - 1/x)`
`= {(x - 1/x)^3 + 3.x.1/x(x - 1/x)}`
`= {(x - 1/x)^2 + 2.x.1/x} - (x - 1/x)`
`= {2^3 + 3.2} {2^2 + 2} - 2`
`= (8 + 6) (4 + 2) - 2`
`= (14 xx 6) - 2`
`:. x^5 - 1/x^5 = 82` (প্রমাণিত)